A Systematic Review of the Microbiome in Children With Neurodevelopmental Disorders - Lacorte, Eleonora; Gervasi, Giuseppe; Bacigalupo, Ilaria; Vanacore, Nicola; Raucci, Umberto; Parisi, Pasquale (Frontiers in Neurology, 2019)
Background and Purpose: Relationship between gut microbiome and central nervous system, have been suggested. The human microbiome may have an influence on brain’s development, indicating that dysbiosis may contribute in the etiology and progression of some neurological/neuropsychiatric disorders. The objective of this systematic review was to identify evidence on the characterization and differentiation of the microbiome in children with neurodevelopmental disorders, as compared to healthy children. Methods: The review was performed following the methodology described in the Cochrane handbook for systematic reviews, and was reported based on the PRISMA statement for reporting systematic reviews and meta-analyses. All literature published up to June, 2018 was retrieved searching the databases PubMed, ISI Web of Science and the Cochrane Database of Systematic Reviews. Only observational studies, published in English and reporting data on the characterization of the microbiome in humans aged 0-18 years with a neurodevelopmental disorder were included. Neurodevelopmental disorders were defined according to the definition included in the Diagnostic and Statistical Manual of Mental Disorders, version 5 (DSM–V). Results: Bibliographic searches yielded 9229 records. One study was identified through other data sources. A total of 12 studies were selected based on their relevance and pertinence to the topic of the review, and were then applied the predefined inclusion and exclusion criteria. A total of 6 case-control studies met the inclusion criteria, and were thus included in the qualitative analysis and applied the NOS score. Two studies reported data on the gut microbiome of children with ADHD, while 4 reported data on either the gut (n=3) or the oral microbiome (n=1) of children with ASD. Conclusions: All the six studies included in this review showed a high heterogeneity in terms of sample size, gender, clinical issues, and type of controls. This high heterogeneity, along with the small sample size of the included studies, strongly limited the external validity of results. The quality assessment performed using the NOS score showed an overall low to moderate methodological quality of the included studies. To better clarify the potential role of microbiome in patients with neurodevelopmental disorders, further high-quality observational (specifically cohort) studies are needed.